Analisis Deterensi Asimetris pada Pengembangan Anti-Satellite (ASAT) oleh Tiongkok Terhadap Dominasi Amerika Serikat (AS) - Widnyana, I Gede Wahyu; Resen, Putu Titah Kawitri Resen; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2020): Hubungan Internasional Vol1, No1, th 2020, 2020)
ABSTRACT This research aims to describe and prove whether Anti-Satellite (ASAT) technology has developed by China is deterrence to US in term of Space Race issue or not. In 2007, China officially announced their succession on ASAT development test. The phenomena suddenly became a hot issue among countries, due to the hiatus of ASAT power for at least 20 years from world dispute. The rising of China’s ASAT is interesting to be discussed, because the US as dominant authority of outer space perceived the China’s ASAT as a threat. The emergent issue between China and the US is related to International Relation Studies, especially deterrence concept. The researcher uses asymmetrical deterrence theory proposed by Frank C. Zagare, on aiming to prove deterrence committed by China through ASAT development. According to the result of synthetic analysis, the researcher found the answer that China’s ASAT development is a form of deterrence. Keywords: China, the US, deterrence, ASAT